PENGARUH KETINGGIAN DAN HABITAT TERHADAP KERAGAMAN KUMBANG KOPROFAGUS (COLEOPTERA: SCARABAEIDAE) DI JALUR PENDAKIAN APUY DAN LINGGARJATI, TAMAN NASIONAL GUNUNG CIREMAI - Noerdjito, Woro A. (JURNAL BIOLOGI INDONESIA, 2009)
ABSTRACTThe influence of altitude and habitat to Coprophagous beetles diversity (Coleoptera: Scarabaeidae)at two site (Apuy and Linggarjati) of Gunung Ciremai National Park. As a newNational Park, the data about insects diversity from Gunung Ciremai and surrounding areas arelack especially about the influence of altitude and habitat to Coprophagous beetles.Coprophagous beetles is important to the ecological process related to nutrient cycling andsoil aeration, dispersal of seeds deficated by frugivorous and phoretic mites. The mostimportance the coprofagous beetles was very sensitive to environment or habitat changesespecially the vertebrate where they live within. Coprophagous beetles as forest indicatorcause of their behaviors and primary correlated with the population of the vertebrate faunas inhabitat conditions. This study aims to know the impact of altitude and habitat to thecoprophagoes beetles community in two forest areas (Apuy and Linggarjati), Gunung CiremaiNational Park. Totally 15 species (1089 specimens) of coprophagoes beetles collected byhuman dung traps and dominated by Onthophagus luridipennis (603 specimens).Key words: Coprophagous beetles, habitat, altitude and Ciremai